2009
DOI: 10.1177/096369350901800102
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling of Circular Glare Laminated Plates under Lateral Indentation

Abstract: INTRODUCTION GLARE is a Fibre-Metal Laminated material used in aerospace structures which are frequently subjected to various impact damages [1-5]. A high percentage of the total energy absorbed by GLARE plates during impacts is due to the static deformation of the plate [1, 6-7]. Hence, response of GLARE plates subjected to lateral indentation is very important as far as their overall impact behaviour is concerned. This paper deals with the static response of thin circular clamped GLARE fibre-metal laminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(65 citation statements)
references
References 8 publications
1
64
0
Order By: Relevance
“…5,28,31,32 In this article, by examining FEM plots of lateral plate deflections, it is found with very good accuracy that thin circular clamped GLARE plates under the simultaneous application of radial preloading and lateral indentation have also axisymmetrical deflection shape. In Figure 7, representative lateral deflections plot of a preloaded GLARE plate is depicted.…”
Section: Analytical Calculation Of the Preloading Strain Energymentioning
confidence: 92%
See 1 more Smart Citation
“…5,28,31,32 In this article, by examining FEM plots of lateral plate deflections, it is found with very good accuracy that thin circular clamped GLARE plates under the simultaneous application of radial preloading and lateral indentation have also axisymmetrical deflection shape. In Figure 7, representative lateral deflections plot of a preloaded GLARE plate is depicted.…”
Section: Analytical Calculation Of the Preloading Strain Energymentioning
confidence: 92%
“…Solutions of similar problems have been published in the literature 5,10,28,29 but without any preloading. The work of Vlot, 6 deals with the impact response of preloaded fiber-metal laminates.…”
Section: Introductionmentioning
confidence: 90%
“…From the experimental data in reference [1] it is concluded that GLARE plates subjected to lateral indentation will undergo very large deflections, several times the plate thickness, before first failure due to tensile fracture of glass-epoxy occurs. It was concluded in [8] that, for large plate deflections, P during loading can be calculated up to the point of first failure considering only one Ritz parameter and only the membrane stiffness of the GLARE plate. This conclusion will be used here for the calculation of P during loading.…”
Section: Analytical Modellingmentioning
confidence: 99%
“…The first failure load and deflection can be calculated using the corresponding analytical formulas derived in reference [8]. Remaining assumptions concerning the calculation of P during loading and the point of first failure made in [8] are considered valid. The maximum applied indentation is considered to be less than the first failure deflection.…”
Section: Analytical Modellingmentioning
confidence: 99%
See 1 more Smart Citation